Lignicolous freshwater fungi in China III: Three new species and a new record of Kirschsteiniothelia from northwestern Yunnan Province - D. F. Bao (2018)
© Guizhou Academy of Agricultural Sciences. The diversity of lignicolous freshwater fungi of China is currently being studied. In this paper, fresh collections of Kirschsteiniothelia species from submerged wood in northwestern Yunnan Province, China, were reported. The phylogenetic analyses of combined ITS, LSU and SSU sequence data placed the isolates of the taxa within the family Kirschsteiniotheliaceae. Three new species, Kirschsteiniothelia aquatica, K. cangshanensis and K. fluminicola are introduced, based on their distinct morphology and evidences from molecular phylogeny. A detailed description of Kirschsteiniothelia rostrata, a new record for China is provided.